2022
DOI: 10.1155/2022/9621893
|View full text |Cite|
|
Sign up to set email alerts
|

Diagnosis of Cervical Intraepithelial Neoplasia and Invasive Cervical Carcinoma by Cervical Biopsy under Colposcopy and Analysis of Factors Influencing

Abstract: Objective. To explore the diagnosis of cervical intraepithelial neoplasia (CIN) and invasive cervical carcinoma (ICC) by cervical biopsy under colposcopy and analyze the factors influencing the detection. Methods. The clinical data of 134 CIN confirmed by colposcopy biopsy in our hospital from June 2018 to October 2019 and subsequent LEEP treatment were analyzed retrospectively. All patients were diagnosed pathologically after the operation. The diagnosis of CIN by cervical biopsy under colposcopy was observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…A study reported that image quality of colposcopy images, atypical blood vessels, biopsy sampling method, and visible lesion area of the cervix were independently associated with CC after surgery for CIN3 [ 12 ]. These factors above can be subjective and dependent upon the physician’s experience.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A study reported that image quality of colposcopy images, atypical blood vessels, biopsy sampling method, and visible lesion area of the cervix were independently associated with CC after surgery for CIN3 [ 12 ]. These factors above can be subjective and dependent upon the physician’s experience.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, guidelines advocate the surgical removal of CIN3 lesions [ 2 , 4 , 9 ]. Indeed, a pathological upgrade to CC can be observed after surgery in about 10-11% of the patients [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%